Miscarriage rates after dehydroepiandrosterone (DHEA) supplementation in women with diminished ovarian reserve: a case control study - Weghofer Andrea; Ryan Eddy; Gleicher Norbert; Blanco-Mejia Sonia; Barad David H (BMC, 2009)
Abstract Background Dehydroepinadrosterone (DHEA) supplementation improves pregnancy chances in women with diminished ovarian reserve (DOR), by possibly reducing aneuploidy. Since a large majority of spontaneous miscarriages are associated with aneuploidy, one can speculate that DHEA supplementation may also reduce miscarriage rates. Methods We retroactively compared, utilizing two independent statistical models, miscarriage rates in 73 DHEA supplemented pregnancies at two independent North American infertility centers, age-stratified, to miscarriages reported in a national U.S. in vitro fertilization (IVF) data base. Results After DHEA supplementation the miscarriage rate at both centers was 15.1% (15.0% and 15.2%, respectively). For DHEA supplementation Mantel-Hänszel common odds ratio (and 95% confidence interval), stratified by age, was significantly lower, relative to odds of miscarriage in the general IVF control population [0.49 (0.25-0.94; p = 0.04)]. Miscarriage rates after DHEA were significantly lower at all ages but most pronounced above age 35 years. Discussion Since DOR patients in the literature are reported to experience significantly higher miscarriage rates than average IVF patients, the here observed reduction in miscarriages after DHEA supplementation exceeds, however, all expectations. Miscarriage rates after DHEA not only were lower than in an average national IVF population but were comparable to rates reported in normally fertile populations. Low miscarriage rates, comparable to those of normal fertile women, are statistically impossible to achieve in DOR patients without assumption of a DHEA effect on embryo ploidy. Beyond further investigations in infertile populations, these data, therefore, also suggest the investigations of pre-conception DHEA supplementation in normal fertile populations above age 35 years.